Tanda Tangan Elektronik dalam Akta Pernyataan Keputusan Rapat Umum Pemegang Saham Perseroan Terbatas - Ni Kadek Sofia Arianti; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Interpretasi Hukum, 2020)
This research is motivated by the development of technology playing an important role in the establishment of companies in various regions in the territory of the archipelago, namely the Republic of Indonesia, one of which is a Limited Liability Company. This study aims to determine the arrangement of electronic signatures in the General Meeting of Shareholders of Limited Liability Companies and to find out the legal consequences of the signatures conducted electronically in the deed of decree of the General Meeting of Shareholders of Limited Liability Companies. The method used in this research is the normative research approach is legislation. Then, the data that has been analyzed are presented in an informal form, through the words described in paragraphs. The results of this study address that the regulation of electronic signatures in the deed of the decision of the decision of the general meeting of shareholders of the Limited Liability Company through tracing and transformation according to structured translation by reasoning based on logic that electronic information or electronic documents and / or printouts can be used as evidence legal law, which is also an expansion of legal legal evidence based on the provisions of article 11 jo. Article 5 of the Law. Therefore, the evidence according to the procedural law above made in the form of electronic information or electronic documents, is valid evidence under the Electronic Information and Transaction Law, so that all electronic transactions that utilize electronic media produce electronic signatures that are loaded on the deed of determination of the results of the GMS decision, the Limited Liability Company can be considered as a deed. Then, due to the legal signature that was carried out through electronic media the outcome of the determination of the GMS had a legal impact on the legalization status of the deed which according to the relevant Act was declared valid insofar as the deed was seen as a deed under the hand.